On the Issue of Studying the Functional Features of the Body of Student-Sportsmen in the Conditions of the Republic of Karakalpakstan - Sultansuinov A.S. (Zien Journals, 2022)
The article deals with the issues of studying the functional characteristics of the body of student-sportsmen in the conditions of the Republic of Karakalpakstan. It is noted that the system-forming factor of functional reserves indicates the results of activities that ensure the adaptation of the body of student-sportsmen to various physical loads. It was found that the level of cardiac synchronization characterizes the degree of vegetative balance.
Keywords: Karakalpakstan; the body of student-sportsmen; range of reliability; adaptation process